2016
DOI: 10.1097/fpc.0000000000000238
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacogenetics of efavirenz discontinuation for reported central nervous system symptoms appears to differ by race

Abstract: Background Efavirenz frequently causes central nervous system (CNS) symptoms. We evaluated genetic associations with efavirenz discontinuation for CNS symptoms within 12 months of treatment initiation. Methods Patients had initiated efavirenz-containing regimens at an HIV primary care clinic in the southeastern United States, and had at least 12 months of follow-up data. Polymorphisms in CYP2B6 and CYP2A6 defined efavirenz metabolizer categories. Genome-wide genotyping allowed adjustment for population strat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 40 publications
1
23
0
1
Order By: Relevance
“…Indeed, studies have shown that individuals with higher genetic risk scores for slow EFV metabolization, including cumulative CYP2B6 , CYP2A6 and CYP3A4 variant alleles, had a significantly higher risk of EFV discontinuation for reported CNS symptoms than individuals with lower genetic risk scores . In the aggregate AIDS Clinical Trials Group (ACTG) clinical trials data which demonstrated an excess of suicidality (i.e.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, studies have shown that individuals with higher genetic risk scores for slow EFV metabolization, including cumulative CYP2B6 , CYP2A6 and CYP3A4 variant alleles, had a significantly higher risk of EFV discontinuation for reported CNS symptoms than individuals with lower genetic risk scores . In the aggregate AIDS Clinical Trials Group (ACTG) clinical trials data which demonstrated an excess of suicidality (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…However, the long‐term efficacy of EFV‐containing regimens , the low cost of EFV, which is a determining factor for its use in developing countries, and the recent demonstration that a reduced dose of 400 mg is noninferior to the standard dose of 600 mg in combination with tenofovir and emtricitabine as initial HIV therapy, with fewer EFV‐related adverse events , suggest that it will continue to be used world‐wide. In addition, EFV‐induced CNS symptoms, which occur, usually, early in therapy but frequently resolve after several weeks , may be associated with genetic variability in EFV metabolism .…”
Section: Introductionmentioning
confidence: 99%
“…For these patients, there is a “moderate” recommendation to consider initiating efavirenz with a decreased dose of 400 mg/day. CYP2B6 PMs are at greatest risk for higher dose‐adjusted trough concentrations compared with NMs and IMs, and greater overall plasma efavirenz exposure, which puts these patients up to a 4.8‐fold increased risk for adverse effects and treatment discontinuation . For these patients, there is a “moderate” recommendation to consider initiating efavirenz with a decreased dose of either 400 or 200 mg/day.…”
Section: Drug: Efavirenzmentioning
confidence: 99%
“…CYP2B6 PMs are at greatest risk for higher dose-adjusted trough concentrations compared with NMs and IMs, and greater overall plasma efavirenz exposure, which puts these patients up to a 4.8-fold increased risk for adverse effects and treatment discontinuation. [20][21][22][23][24][25][26][27][28][29][30][31] For these patients, there is a "moderate" recommendation to consider initiating efavirenz with a decreased dose of either 400 or 200 mg/day. This "moderate" rather than "strong" recommendation reflects the fact that most CYP2B6 PMs do not discontinue efavirenz 600 mg/day for adverse effects.…”
Section: Linking Genetic Variability To Variability In Drug-related Pmentioning
confidence: 99%
“…Stored DNA from a total of 837 patients who had initiated either atazanavir-containing regimens (including patients in the present association analysis) or efavirenz-containing regimens (from a previous analysis 21 ) was genotyped for 535 543 single nucleotide polymorphisms, including rs887829 C→T, by Illumina HumanCore Exome assay (San Diego, California, USA). Genotype call rates exceeded 99% for 807 samples, including 349 individuals for the current analysis.…”
Section: Methodsmentioning
confidence: 99%